Pregnancy outcomes in women aged 40 years or older - Shahla Yazdani; Zinatosadat Bouzari; Atefeh Yadollahzadeh (Babol University of Medical Sciences, 2015)
Introduction: Many women nowadays postpone their first pregnancy to the fourth or fifth decades of their lives, which could emanate from social, economic and educational factors. This study was an attempt to evaluate the pregnancy and neonatal outcomes in women at 40 years of age or above. Methods: In this retrospective study, we compared the pregnancy outcomes for women over the aged 40 with those of age group under the age of 40 years. The maternal and obstetrical data, from August 2009 to August 2013, were all obtained from hospitals obstetrical documents. The Chi-square test and the T-Test were used to determine the relationship between the qualitative and the quantitative variables. Results: During the four years, a total number of 160 women, aged 40 or above gave birth, among which 25% was nulliparous. The mean age at delivery for the elderly group was 42.4 ± 2.1, which can be compared with the mean age of women (26.7± 4.7) under the age of 40. The gestational diabetes (p= 0.0001), gestational hypertension (p = 0.022), and polyhydramnios (p=0.010) occurred more often in women aged 40 or above. It is worth mentioning that the occurrence of anemia in the third trimester in the elderly group was lower than that of the younger group (8.8% vs. 23.1%) (p= 0.024). The preeclampsia, preterm labor, low birth weight, oligohydramnios, bleeding, emergency Cesarean section, and urinary tract infection were all similar in the two age groups. Conclusion: This study showed that the adverse pregnancy outcomes were significantly higher in the women aged 40 years or above when compared with those of younger women. Therefore, there is an urgent need to provide more frequent prenatal care for the elderly women in primary health care centers.